BAHASA RUPA TRADISI DALAM LUKISAN KACA KONTEMPORER KARYA HARYADI SUADI TAHUN 1989-2011 - Indah Rosniawati (Universitas Komputer Indonesia, 2018)
Every artists studies art from society tradition. That is every creation are tradition assets a society, at he begining constitue creation of creative on new creation at period. The strength of visual artist thinks with visual language. Visual language can use for expressing many kinds of visual tradition art. Focus to research that is in tended to creation painting glass Haryadi, because the elements visual as produce inelined. Disposed to become very free but constant for remind the elements of visual language tradition Haryadi to become artist contemporer since following research visual language with Primadi Tabrani. So that to become Haryadi Contemporer in his tradition. The background Haryadi in glass painting is one of living to creation art glass painting to the elements tradition painting glass Haryadi in that periode at 1989-2011 to take the element tradition pupet, batik, culture Cirebon, Cina, Jawa, Islam, Hindu and from the elements visual language Haryadi only getting shapes his visual only is comoted in art creation. Haryadi didn't take throughly the tradition of elements, except visual language tradition.